Hardware-in-Loop Simulation for the Energy Management System Development of a Plug-in Hybrid Electric Bus. (June 2016) - Yi, Lu; He, Hongwen; Peng, Jiankun
Abstract: In this paper, a hardware-in-loop experiment that integrated controller area network (CAN) monitor and evaluation function for control system is the research content, and a rule-based energy management system of plug-in hybrid electric bus (PHEB) is developed. The real-time kernel of PHEB model was downloaded into VTSystem platform for the real-time simulation system development. An driver and energy management system-in-loop experiment was carried out to verify the energy management strategy under the China Transit Bus Driving Cycle (CTBDC), and the CAN bus performance features were evaluated by CANoe software. The energy consumption per 100 km includes 14.1L diesel and 11.9 kW·h electricity with an initial SoC of 85%.